2013
DOI: 10.1038/ncomms2643
|View full text |Cite
|
Sign up to set email alerts
|

Trunk exoskeleton in teleosts is mesodermal in origin

Abstract: The vertebrate mineralized skeleton is known to have first emerged as an exoskeleton that extensively covered the fossil jawless fish. The evolutionary origin of this exoskeleton has long been attributed to the emergence of the neural crest, but experimental evaluation for this is still poor. Here we determine the embryonic origin of scales and fin rays of medaka (teleost trunk exoskeletons) by applying long-term cell labelling methods, and demonstrate that both tissues are mesodermal in origin. Neural crest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 42 publications
(58 reference statements)
8
96
0
Order By: Relevance
“…New insights gained from the comparative studies in amphioxus imply the primordial role of somites over neural crest cells in the evolutionary origin of vertebrate skeletal tissues. This idea is consistent with recent findings that the trunk dermal skeletal elements (such as teleost scales and fin rays) are derived from the mesoderm instead of neural crest cells [65 ]). The chondrogenic developmental program in the vertebrate neural crest did not evolve de novo, but is, instead, co-opted in a mosaic manner from a pre-existing chondrogenic repertoire present in the somite and its derivatives.…”
Section: Discussionsupporting
confidence: 92%
“…New insights gained from the comparative studies in amphioxus imply the primordial role of somites over neural crest cells in the evolutionary origin of vertebrate skeletal tissues. This idea is consistent with recent findings that the trunk dermal skeletal elements (such as teleost scales and fin rays) are derived from the mesoderm instead of neural crest cells [65 ]). The chondrogenic developmental program in the vertebrate neural crest did not evolve de novo, but is, instead, co-opted in a mosaic manner from a pre-existing chondrogenic repertoire present in the somite and its derivatives.…”
Section: Discussionsupporting
confidence: 92%
“…Although elasmoid scales of teleost fishes arise from mesoderm (Lee et al 2013;Mongera and Nüsslein-Volhard 2013;Shimada et al 2013), it cannot be excluded that both mesoderm-derived and neural crest-derived mesenchymal cells contribute to the formation of more ancestral types of scales such as tooth-like placoid scales of cartilaginous fishes (Green et al 2015). As mentioned above, electrosensory ampullary organs are derived from lateral line placodes in cartilaginous fishes (Gillis et al 2012;Baker et al 2013), not neural-crest derived as previously reported (Freitas et al 2006).…”
Section: Discussionmentioning
confidence: 71%
“…31, 32), it was hypothesized that these fins share a common positional value and patterning mechanism (the so‐called Dorsal + Anal fin patterning module, proposed by Mabee et al, 2002). It is known that the median fin rays and their primordial cells are derived from the somite in medaka (Shimada et al, 2013), suggesting that the anal and dorsal fins of zebrafish and goldfish are also derived from somite derivatives. In summary, it is expected that the anal and dorsal fin rays may be derived from somite‐derived cells in both zebrafish and goldfish, but the timing of mesenchymal cell differentiation has altered between these two lineages.…”
Section: Discussionmentioning
confidence: 99%